The Saliva Proteome of Dogs: Variations Within and Between Breeds and Between Species. Issue 3 (23rd February 2018) - Pasha, Sabah; Inui, Taichi; Chapple, Iain; Harris, Stephen; Holcombe, Lucy; Grant, Melissa M.
Abstract: Saliva is a complex multifunctional fluid that bathes the oral cavity to assist in soft and hard tissue maintenance, lubrication, buffering, defense against microbes, and initiating digestion of foods. It has been extensively characterized in humans but its protein composition in dogs remains poorly characterized, yet saliva composition could explain (patho) physiological differences between individuals, breeds and with humans. This pilot discovery study aimed to characterize canine saliva from two breeds, Labrador retrievers and Beagles, and to compare this with human saliva using quantitative mass spectrometry. The analysis demonstrated considerable inter‐individual variation and difference between breeds; however these were small in comparison to the differences between species. Functional mapping suggested roles of detected proteins similar to those found in human saliva with the exception of the initiation of digestion as salivary amylase was lacking or at very low abundance in canine saliva samples. Many potential anti‐microbial proteins were detected agreeing with the notion that the oral cavity is under continuous microbial challenge.